Ensuring the Security of Foreign Nationals through Registration - Bekhbat, Ochgerel (Mongolian Journal of Strategic Studies, 2025)
In recent years, Mongolia has actively pursued policies aimed at promoting foreign investment, labor force, and tourism in order to support economic growth and advance national development. As part of these efforts, creating a favorable environment for foreign nationals has become a key priority. Consequently, there is a growing necessity to modernize, digitize, and enhance the efficiency of the registration system for foreign nationals in accordance with international standards. To improve the registration system, the legal environment has been revised, and in 2020, the Parliament of Mongolia adopted several amendments to the Law on the Legal Status of Foreign Nationals, particularly concerning the registration processes and requirements for foreign citizens. Establishing a reliable registration system for foreign nationals residing in Mongolia—whether for official, personal, or short-term purposes—is of critical importance for ensuring their security, pre venting crime and legal violations, and enabling effective emergency response in the event of natu ral disasters or other force majeure situations. Furthermore, it contributes to the broader goals of protecting national security and public order. Accordingly, this study examines the legal framework, policy orientation, and current implementa tion practices concerning the registration and oversight of foreign nationals, with a comparative perspective drawn from the experiences of Singapore and Canada. It further identifies key chal lenges facing the system and offers policy recommendations and practical measures to improve its effectiveness and alignment with international best practices. Гадаадын иргэдийн аюулгүй байдлыг бүртгэлээр дамжуулан хангах нь Хураангуй: Сүүлийн жилүүдэд Монгол Улс эдийн засгийн өсөлтөө дэмжих, хөгжлийн түвшинг ахиулах зорилгоор гадаадын хөрөнгө оруулалт, ажиллах хүч, аялал жуулчлалыг дэмжихэд чиглэсэн бодлогыг тууштай хэрэгжүүлж, гадаадын иргэдэд таатай нөхцөл бүрдүүлэхийг зорьсоор ирсэн. Энэхүү бодлогын хүрээнд гадаадын иргэдийн бүртгэлийн тогтолцоог олон улсын жишигт нийцүүлэн шинэчлэх, цахимжуулах, үр ашигтай болгох зайлшгүй шаардлага тулгарч байна. Бүртгэлийн тогтолцоог сайжруулах зорилгоор хууль эрх зүйн орчны шинэчлэл хийж, 2020 онд УИХ-аас Гадаадын иргэний эрх зүйн байдлын тухай хуульд гадаадын иргэнийг бүртгэх, бүртгүүлэх үйл явцтай холбогдсон хэд хэдэн нэмэлт, өөрчлөлт оруулсан. Монгол Улсад албан болон хувийн хэргээр оршин сууж буй болон түр ирэгч гадаадын иргэдийн шилжилт хөдөлгөөн, урсгал, төвлөрлийг бүртгэлжүүлэх нь тэдний аюулгүй байдлыг хангах, гэмт хэрэг, зөрчлөөс урьдчилан сэргийлэх, байгалийн гамшиг, давагдашгүй хүчин зүйл тохиолдсон онцгой нөхцөлд хариу арга хэмжээ шуурхай авч хэрэгжүүлэх, үндэсний аюулгүй байдлыг хангах чухал ач холбогдолтой юм. Иймд энэхүү судалгаа нь Сингапур, Канад Улсын жишээг харьцуулан авч үзэж, Монгол Улсад гадаадын иргэдийн бүртгэлийн тогтолцоог боловсронгуй болгох чиглэлээр хууль эрх зүйн зохицуулалт, бодлогын чиг хандлага, хэрэгжилтийн байдал болон тулгамдаж буй асуудлыг тодорхойлон дүгнэж, цаашид авч хэрэгжүүлэх боломжит арга хэмжээг санал болгоход чиглэнэ. Түлхүүр үг: бүртгэлийн тогтолцоо, 48 цагийн бүртгэл, хууль эрх зүйн орчин, аюулгүй байдал